Trends of intentional drug overdose among youth: a population-based cohort study. (2nd July 2020) - Gilley, Meghan; Sivilotti, Marco L. A.; Juurlink, David N.; Macdonald, Erin; Yao, Zhan; Finkelstein, Yaron
Abstract: Background: Intentional overdose is the commonest form of self-harm in adolescents globally. We explored temporal trends in intentional overdose among youth. Methods: Using multiple linked healthcare databases, we conducted a population-based cohort study in Ontario, Canada, from 2002 to 2015. We included all patients aged 8 to 19 years who presented to an emergency department (ED) or were hospitalized for intentional overdose, stratifying by age and agent(s) consumed. We determined the annual rate of intentional overdose over time. For context, we contrasted these data against the annual rate of select unintentional injuries (laceration of face or scalp, upper extremity fracture, and accidental burn) in the same group over the same period. Results: We identified 31, 419 unique intentional overdose events in youth, with a striking U-shaped trend apparent over the study period. From 2002 to 2010, hospital presentations for intentional overdose gradually declined. However, from 2010 to 2015, ED visits increased by 75% and hospital admissions doubled. The sharpest increases were observed in adolescents aged 14 to 17 years, and the most commonly implicated substances were acetaminophen, antidepressants and Non-Steroidal Anti-Inflammatory Drugs (NSAIDs). Over the study period, intentional overdoses involving antidepressants nearly doubled and those involving acetaminophen increased by 50%. In contrast, we observed steady and sustained declines in rates of hospital care for unintentional injuries in the same population over the same period. Conclusions: Since 2010, intentional overdoses have increased among youth, while other forms of unintentional injury have continued to decline. Further research is needed to understand the reasons for the unexpected rise in intentional overdose in adolescents, and strategies developed to mitigate this phenomenon.